Unfair Business Practices of the “Internet Giants” and the abusive de-indexing procedure of Google Adwords: An Analysis of French and EU Law - Behar-Touchais, Martine (Law, State and Telecommunications Review, 2020)
Objective ”“ The article explores the new unfair business practices of “Internet giants” with a focus on judicial and administrative precedents. Unfair commercial practices can happen in two ways: about consumers; and, concerning professional advertisers. The digital platforms ”“ especially Google Adwords ”“ have been under legal scrutiny by several courts and authorities, as the paper describes. Methodology/approach/design ”“ The article has bibliographical and jurisprudential research on the unfair commercial practices of Internet giant companies, with emphasis on Google Adwords service. The selected cases come from the French courts and the Court of Justice of the European Union. After careful analysis, it is possible to determine lines of legal differentiation between the types of unfair commercial practices. Findings ”“ The article concludes that the construction of a legal principle as duty of loyalty of digital platforms towards consumers and professional participants is an important advance. Thus, both European Union law and French law are in evolution, since they have foreseen this principle. However, for this principle to be effective, administrative and judicial action will be necessary. At the European Union level, this duty of loyalty must play a central role within the comprehensive set of public policies of the Digital Single Market. Practical implications ”“ The article has practical implications, since it describes cases from France and the European Union, which are useful to understand both the Brazilian and the global situation. The commercial operations of Internet giant companies are transnational. Thus, it is useful to know how France and the European Union are labeling some certain commercial practices as unfair. Originality/value ”“ There is no text in Portuguese that has carried out a survey of the French and European Union case law regarding unfair commercial practices of Internet giant companies. The text also helps to understand the joint application of French commercial and competition law in correlation with European Union law.